Dinosaur train. Dinosaurs big + small! [videorecording (DVD)] - Bartlett, Craig; Izumi, Terry (Dinosaur train, 2019)
Learn all about dinosaurs of different shapes and sizes. Join the gang for ten fun adventures big and small where they discover a new species, meet a small mammal friend, and lots more.